RESEARCH OF THE TEARING CHARACTERISTICS OF PARARAMID YARN - ДМИТРИК, О. М.; БОБРОВА, С. Ю.; ГАЛАВСЬКА, Л. Є.; ЄЛІНА, Т. В. (Technologies and Engineering, 2023)
Purpose. Identify the factors affecting the strength characteristics of complex para-aramid yarns. Methodology. The work uses a standardized method of research the tearing characteristics of yarns according to DSTU ISO 2062:2004 using a breaking machine WDW-5ES, the basic provisions of textile material science and the theory of knitting, methods of analysis and synthesis of the obtained results. Results. In order to identify the factors that influence the tearing characteristics of PA threads, during experimental studies, the number of yarns subject to breaking, the clamping length and interweaving yarns point in relation to the movable clamp were changed in the case of testing the yarn strength by loop. At the same time, the clamping length varied in the range from 25 mm to 300 mm. In the event of a yarn breaking by loop, the clamping length remained unchanged and was 100 mm, and the location of the point of yarns interweaving in relation to the clamps was determined as 25x75mm, 50x50mm, 75x25mm. Scientific novelty. The regularities of the influence of the number of yarns susceptible to breaking, the clamping length and the location of the interweaving point in the case of the study of the yarn strength at the loop break on the tensile strength and elongation have been established. Practical significance. The obtained research results on the nature of the destruction of the complex para-aramid yarn under the breaking force can be used in computer simulation systems during the implementation of virtual experiments to determine the physical and mechanical characteristics of knitwear based on its 3D model.